PENGARUH USAHA BUDIDAYA SARANG BURUNG WALET TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT KAMPUNG MERANCANG DI KABUPATEN BERAU - Rifai, Ahmad (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
This study aims to analyze the influence of swiftlet nest farming on the income improvement of the community in Merancang Village, Berau Regency. The research employed a quantitative approach with a survei method involving 30 swiftlet farmers selected through total sampling. Data were collected using a structured questionnaire and analyzed through validity, reliability, and normality tests, as well as simple linear regression and t-test. The results show a strong positive relationship between swiftlet nest farming and community income improvement, with a correlation coefficient of 0.839. The regression equation obtained is Y = 7.087 + 0.969X, indicating that each one-unit increase in swiftlet nest farming contributes to a 0.969-unit increase in community income. The t-test result (t-count = 8.168 > t-table = 1.703; sig. = 0.000 < 0.05) confirms that the hypothesis is accepted. Thus, swiftlet nest farming significantly contributes to enhancing the income and economic well-being of the local community.